Analisis Desain dan Keandalan Bejana Bertekanan pada Industri Energi Pendekatan Numerik dan Eksperimental - Jefri Imron (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Pressure vessels are critical components in the energy industry, used to store and process high-pressure fluids. The structural reliability of these vessels plays a pivotal role in ensuring operational safety and system efficiency. This study aims to analyze the design and reliability of pressure vessels using both numerical and experimental approaches to optimize performance and enhance safety factors. The numerical method was conducted through Finite Element Analysis (FEA) using ANSYS software to evaluate stress distribution, stress concentration, and potential failure modes under various operational load scenarios. Meanwhile, the experimental method involved hydrostatic pressure testing, strain measurements using strain gauges, and displacement analysis to validate the numerical simulation results. Data were collected from simulations and laboratory experiments, then analyzed quantitatively by comparing key parameters such as stress distribution, deformation patterns, and safety factors against industry standards. The results indicate that combining numerical and experimental approaches improves the accuracy of pressure vessel behavior predictions, enables more efficient design optimization, and enhances structural reliability. In conclusion, the methods applied in this study can serve as a reference for developing safer, more efficient pressure vessel designs that comply with industrial standards, thereby supporting improved safety and operational efficiency in the energy sector.